In-situ thermally-reduced graphene oxide/epoxy composites: thermal and mechanical properties - Olowojoba,GB; Eslava,S; Gutierrez,ES; Kinloch,AJ; Mattevi,C; Rocha,VG; Taylor,AC (Applied Nanoscience, 2016)
Graphene has excellent mechanical, thermal, optical and electrical properties and this has made it a prime target for use as a filler material in the development of multifunctional polymeric composites. However, several challenges need to be overcome in order to take full advantage of the aforementioned properties of graphene. These include achieving good dispersion and interfacial properties between the graphene filler and the polymeric matrix. In the present work we report the thermal and mechanical properties of reduced graphene oxide/epoxy composites prepared via a facile, scalable and commercially-viable method. Electron micrographs of the composites demonstrate that the reduced graphene oxide (rGO) is well-dispersed throughout the composite. Although no improvements in glass transition temperature, tensile strength, and thermal stability in air of the composites were observed, good improvements in thermal conductivity (about 36%), tensile and storage moduli (more than 13%) were recorded with the addition of 2 wt% of rGO.